An Easy-to-Use Search Tool for the Abbottabad Compound Material Archive - Mantua, Janna (Perspectives on terrorism, 2023)
Osama Bin Laden’s compound in Abbottabad, Pakistan was raided following his death in 2011. The documents retrieved from his compound became known as the Abbottabad Compound Material (ACM). The majority of ACM documents were declassified and released to the public in 2017. However, these documents have not been thoroughly mined by academic researchers despite potentially important information that may exist in the ACM. Academic researchers may be deterred from using the ACM because the documents are not easily accessible or because the documents are predominantly in Arabic. This paper presents a search engine specifically built for researchers that will enable the mining of ACM documents. The ACM search tool may facilitate critical terrorism- and extremism-related research related to al-Qaeda and related terrorist groups.